Characterization of Suicide and Deliberate Self-Harm Among Children in the United States. (January 2019) - McCluskey, Casey K.; Allareddy, Veerajalandhar; Rampa, Sankeerth; Allareddy, Veerasathpurush; Rotta, Alexandre T.
We analyzed data from the Nationwide Emergency Department Sample (NEDS) database for the years 2008 to 2013 to characterize deliberate self-harm among children and adolescents presenting to an emergency department (ED) in the United States. All ED visits for patients aged 19 years or younger involving any self-inflicted injuries were selected. We identified 594 658 ED visits involving self-harm. The majority of patients were female (65.8%), and between ages 16 and 19 years (62.6%). Most were treated and released from the ED (44.9%). The most common mechanisms involved injury by cutting/piercing instruments (26.4%) or poisoning by analgesics or antipyretics (21.5%). There was decrease in ED visits involving 16 to 19 year olds (−8%), and an increase in visits involving 13 to 15 year olds (+45%), 11 to 12 year olds (+94%), and 10 year olds or younger (16%). Our findings highlight a new vulnerable younger population at risk for self-inflicted injuries.